Serum uromodulin predicts graft failure in renal transplant recipients. (17th February 2017) - Steubl, Dominik; Block, Matthias; Herbst, Victor; Schlumberger, Wolfgang; Nockher, Andreas; Angermann, Susanne; Schmaderer, Christoph; Heemann, Uwe; Renders, Lutz; Scherberich, Jürgen
Abstract: Objective and methods: Test the ability of serum uromodulin concentrations 1–3 months after renal transplantation to predict all-cause mortality (ACM) and graft loss (GL) in 91 patients. Results: uromodulin predicted GL equivalently to the other markers studied: the risk for GL was reduced by 0.21 per one standard deviation (SD) increase (cystatin C: hazard ratio [HR] 4.57, creatinine: HR 4.53, blood-urea-nitrogen [BUN]: HR 2.50, estimated glomerular filtration rate [eGFR]: HR 0.10). In receiver-operating-characteristic (ROC) analysis, uromodulin predicted GL with an area-under-the curve of 0.782 at an optimal cut-off (OCO) of 24.0 ng/ml with a sensitivity of 90.0% and a specificity of 70.2%. Conclusion: Serum uromodulin predicted GL equivalently compared to conventional biomarkers of glomerular filtration.